Strategies for the pharmacological treatment of cancer pain in the new century - Deptała, Andrzej; Magoń, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 2004)
In spite of so many analgesic drugs available today, and the relatively simple and effective guidelines to treat cancer pain published and recommended by the World Health Organization, scientists are still looking for new drugs and new strategies utilizing ”old drugs” with new interest and applications for the pain therapy. The development of cyclooxygenase-2-selective nonsteroidal anti-inflammatory drugs (NSAIDs) and transmucosal fentanyl citrate provide new pharmacologic options for the treatment of cancer pain. Several ongoing studies try to assess the potential role of methadone in treating neuropathic pain. Various combinations of opioid agonists and antagonists, and the switching of opioids and/or their routes of administration may offer improved analgesia with fewer adverse effects. In addition, the spectrum of adjuvant agents for the treatment of neuropathic pain has been extended to various antidepressants. Finally, a more potent generation of bisphosphonates may lead to improved pain relief for patients with bone metastases. There is also a continuous research on the role of the N-methyl-d-aspartate (NMDA) receptor and, specifically on NMDA receptor antagonists that may augment analgesia and combat opioid resistance. As a result of these and similar studies, a reappraisal of analgesic use in well defined groups of patients is considered the way forward to providing better control of analgesia.